Incidence of opioid use disorder in the year after discharge from an emergency department encounter - Brittany E. Punches; Rachel M. Ancona; Caroline E. Freiermuth; Jennifer L. Brown; Michael S. Lyons (Journal of the American College of Emergency Physicians Open)
Abstract Objective Therapeutic opioid exposure is associated with long‐term use. How much later use is due to opioid use disorder (OUD) and the incidence of OUD without preceding therapeutic exposure are unknown. We preliminarily explored the association between emergency department opioid prescriptions and subsequent OUD. Methods This retrospective cohort study queried electronic health records for discharged adult patients in the year before (2014) and after (2016) their first encounter in 2015 at either of 2 EDs in a Midwestern healthcare system. OUD was defined by diagnosis codes and prescription history. Patients with OUD history before the index encounter were excluded. We report OUD incidence within 1 year, with time to first indicator of OUD among those with a repeat health system encounter post index using a Cox proportional hazards model. Secondary outcomes were sources of therapeutic opioid exposure and frequency of risk factors associated with OUD among those who developed OUD. Results Of the 49,904 unique, adult ED patients without history of OUD, 669 (1.3%; 95% CI, 1.2–1.4) had health records indicating OUD within 12 months. The proportion of ED patients with OUD at 12 months was 1.5% (95% CI, 1.2–1.9) if prescribed an opioid at index and 1.3% (95% CI, 1.2–1.4) if not. Of the 669 who developed OUD, 80 (12.0%) were prescribed an opioid at the index ED visit, 54 (8%) received an opioid prescription at a subsequent ED visit, and median time to OUD was 4.5 months (interquartile range 1.6‐7.6, range 0.0–11.9). When controlling for demographics, mental health, and prior opioid prescriptions, there was no difference in OUD incidence between patients who did or did not receive an initial ED opioid prescription (HR, 1.1; 95% CI, 0.9–1.4). Conclusions A small but meaningful proportion of the ED population will develop OUD within 1 year even without ED opioid prescription. Though we found no association between ED opioid prescription and later OUD, further study is warranted given the complexity factors influencing OUD incidence, ongoing ED opioid exposure, and limitations inherent to this study design.